2021
DOI: 10.4271/03-15-01-0004
|View full text |Cite
|
Sign up to set email alerts
|

Knock: A Century of Research

Abstract: Knock is one of the main limitations on increasing spark-ignition (SI) engine efficiency. This has been known for at least 100 years, and it is still the case today. Knock occurs when conditions ahead of the flame front in an SI engine result in one or more autoignition events in the end gas. The autoignition reaction rate is typically much higher than that of the flame-front propagation. This may lead to the creation of pressure waves in the combustion chamber and, hence, an undesirable noise that gives knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 340 publications
(457 reference statements)
0
9
0
Order By: Relevance
“…This phenomenon has been analyzed since the beginning of the internal combustion engine's development. The first works on knock combustion were published in 1921 [2] and 1922 [3], as well as the first history of the mentioned topic [4]. Diagnostics of engine operating conditions in terms of knock combustion concerns not only light vehicle engines [5,6], but also marine applications [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been analyzed since the beginning of the internal combustion engine's development. The first works on knock combustion were published in 1921 [2] and 1922 [3], as well as the first history of the mentioned topic [4]. Diagnostics of engine operating conditions in terms of knock combustion concerns not only light vehicle engines [5,6], but also marine applications [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…To combat global climate change, China has announced the ambitious goal of carbon peak and carbon neutralization . Although electrification is considered the best way to achieve decarbonization in the transport sector, conventional internal combustion engine-powered vehicles will continue to dominate the market in the short term . The most direct route to reduce CO 2 emissions is introducing vehicles with improved fuel efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although electrification is considered the best way to achieve decarbonization in the transport sector, conventional internal combustion engine-powered vehicles will continue to dominate the market in the short term. 2 The most direct route to reduce CO 2 emissions is introducing vehicles with improved fuel efficiency. Gasoline direct injection (GDI) vehicles could help reach a fuel consumption reduction of 15% compared with traditional port fuel injection (PFI) vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that several operating parameters influence the knocking tendency of an internal combustion engine. [5][6][7][8] With the development of CFD (Computational Fluid Dynamics) technology, more and more scholars use simulation methods to investigate the knock of spark-ignition engines. Li et al developed a SAGE model with chemical reaction kinetics to explore the influence of EGR (Exhaust Gas Recirculation) on a high compression ratio engine knock.…”
Section: Introductionmentioning
confidence: 99%
“…13 Based on the existing literature, previously published research mainly focused on exploring the independent influence of each factor of compression ratio, inlet temperature, spark timing, and EGR rate on knock. [5][6][7] However, few studies highlight the contribution rate and importance ranking of compression ratio, inlet temperature, spark timing, and the EGR rate to knock tendency, which brings difficulties to the control and suppression of spark ignition engine knock. Therefore, this article aims to determine the order of multiple parameters to the influence of knock tendency and peak in-cylinder pressure.…”
Section: Introductionmentioning
confidence: 99%